Factors Affecting the General Acceptability of Traditional Foods Served at African Cuisine Luncheon in Moi University, Kenya - Mugalavai, Violet; J, Korir; H, Omutimba; R, Nassir; F, Kiama; A, Onyuna; L, Juma; A, Chemutai; M, Wafula; J, Kamwea; R, Schulz; J, Makomere (Nurture, 2010)
Beliefs and mental images that people create regarding food from a culture that is not their own, are likely to influence their choice of food especially when eating out. The cuisine served comprised of 23 different ethnic foods from various East African communities including the Luo, Luhya, Kikuyu, Kalenjin, Akamba, Swahili and Ugandan. Buffet style of service was used to present food using symbolic artifacts of the various ethnic groups. The research sought to examine customers’ perception of traditional food served at an African cuisine luncheon. The objectives of the study were: to investigate the extent to which customers appreciate traditional foods from different cultures and to establish the extent to which sensory characteristics of traditional cuisines affect their general acceptability. The results revealed that sensory characteristics were a significant determinant of the general acceptability of the various cuisines with most of the customers noting that the cuisine was “moderately acceptable”. The acceptability of traditional cuisines was found to be independent of ethnicity of customers. The positive reaction of customers on the cuisine display and variety meant that there was a gap in the menu items served in the food outlet used in this study. The study recommended that all the food outlets in the various campuses of Moi University should attempt to occasionally provide traditional cuisine.